A Vida e Obra do Professor Doutor Aureliano Baptista da Fonseca - Ângela Catarina Almeida Ferreira (2021)
Five years of memories of the multiple facets of the first Portuguese Dermatologist, Professor Aureliano Baptista da Fonseca, born on the 25th of February, 1915, in the city of Porto. The Faculty of Medicine of the University of Porto witnessed his training, PhD and Teachings as a Professor and, even today, "Os Amores de Estudante" resonate with him, played by successive generations of Tunos. Enthusiastic for the Social nature of medical art, he was a pioneer in the Antivenera Fight for the multiple National and International Hospitals he attended. He belonged to eleven medical societies and received multiple awards. But it was through the lens of a camera, the chords on the piano, and the lines of each written poem, that the artistic legacy of the Professor had been eternalized.